Matching the controller role: individuals vs companies - La Paz, Ariel; Gracia, Daniela; Vásquez, Jonathan (Journal of Business Economics and Management, 2020)
Finding a good match in the C-Suite is critical for maximizing business value and capitalizing on competitive advantages. This study analyzes the roles of controllers in organizational descriptions and executives’ profiles, as they both define the position and craft the profession. This paper proposes a framework to describe and classify the existing controller types based on an extended review and description of the available literature. Then, using a clustering method based on the semisupervised k-means, we mapped a sample of 45 controllers to their dominant profile and contrasted individuals’ characteristics against the companies’ definitions of the role. This study reveals that the understanding of the types of controllers, which is usually presented as a dichotomy, may lead to mismatches between what is needed and what is performed. The clustering analysis reveals a significant mismatch between individuals and the organizations defining the role. The framework and clustering method could be used for multiple purposes, such as evaluating what type of controller an individual is or a company needs, which would improve recruitment processes to achieve better matches. The framework expands the identification of controllers from a dichotomy to a gradual classification and describes four controller profiles. This perspective further describes the role and validates the framework using data mining tools.